Análise de modelos de estimativa da radiação solar global - Bessa, Antonio Ronivon de Oliveira (Universidade Federal Rural do Semi-Árido, 2017)
Solar radiation is the main source of energy for the natural processes that occur on Earth. The estimation and use of this radiation are fundamental for different human activities and for the development of sustainable technologies. In this monograph, we investigate the main aspects of two empirical models of estimation of solar radiation in the literature: in the first, solar radiation is a linear function of sunshine, while in the second it is a power law. Using data from solar radiation and insolation we find the values of the free parameters of these two models.
Analysis of global solar radiation estimation models
Keywords: Radiação solar; Energia solar; Modelos; Solar energy; Solar radiation; Models; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA